CIVIL SOCIETY INSTITUTIONS AND HUMAN RIGHTS (Archive of Conferences, 2021)
Today in Uzbekistan there is a perception that the process of reform is focused on a specific goal, progress and effectiveness depends entirely on certain individuals, specific people. The success of our reforms, the future of our country will depend on what these people will be like, what spiritual, cultural and moral values they will remain faithful to. The task is to create a state-law mechanism that will reliably guarantee the initial equal opportunities for all people to demonstrate and realize their abilities, to meet their needs